Alginate-deoxycholic Acid Interaction and Its Impact on Pancreatic ?-Cells and Insulin Secretion and Potential Treatment of Type 1 Diabetes - Mooranian, Armin; Negrulj, Rebecca; Al-Salami, Hani (Springer New York LLC, 2016)
© 2016. Springer Science+Business Media New York.Introduction: The secondary bile acid, deoxycholic acid (DCA), has been shown to exert membrane stabilising effects on a pH sensitive delivery system for the oral delivery of insulin. However, its potential applications in the microencapsulation of pancreatic ß-cells using hydrogels and polyelectrolytes have not been investigated and may require refined microencapsulating methods. Thus, this study aimed to optimise a newly developed microencapsulating method for pancreatic ß-cell delivery (Ionic-Gelation-Vibrational-Jet-Flow; IGVJF) and examine the effects of DCA incorporation on ß-cells microcapsules, using various excipients. Methods: Ten different formulations were prepared (five controls and five tests containing DCA) utilising different concentrations of water soluble gel, polystyrenes, sodium alginate (SA), polyallylamine, and poly-L-ornithine (PLO), and different microencapsulating methods were screened for most uniform microcapsules. The net flow nozzle size ratio of inner:outer flow through the concentric system was examined for best microcapsules. ß-cell microcapsules for each formulation were analysed for cell biology and functions (insulin at 1 and 60 h), and microcapsules were examined for appearance. Results: The used IGVJF method produced best microcapsules when the inner:outer flow nozzle size is 120/200 µm. In addition, deoxycholic acid addition produced higher cell biological activity and functions, postmicroencapsulation, regardless of excipients’ ratio used. DCA has inhibitory effects on pro-inflammatory cytokine secretion by the microencapsulated cells, while microcapsule size and strength remained similar. Microcapsule morphology and membrane surface characteristics were similar for all formulations with noticeable improvements by DCA addition occurring at the lowest PLO concentrations. Conclusion: An inner:outer nozzle size of 120/200 µm, in the deployed microencapsulating method, in combination with the secondary bile acid deoxycholic acid, produced stable microcapsules with improved cell functionality, suggesting suitability for cell microencapsulation and transplantation.